DEVELOPMENT OF INFORMATION SERVICE APPLICATION RT 07 / RW 10 KECAMATAN BEKASI SELATAN KELURAHAN JAKAMULYA WEBSITE BASED USING PHP AND MYSQL - Dwiparaswati, Windy (Lembaga Pengembangan Kinerja Dosen, 2021)
Neighborhood association 07 is a government-recognized community organization and founded because of the wishes of the community. Until now, the activities of reporting, filing, critique and suggestions are carried out by face-to-face meetings, currently in Indonesia and the world is facing a coronavirus outbreak that forces everyone to stay at home and interact with other people avoid. So that the surrounding community becomes difficult to communicate with the ward unit 07 administrator. The purpose of creating this website is to make it easier for the community to communicate with the ward unit 07 without having to meet in person. Creating the Information Services 07 website uses the SDLC (System Development Life Cycle) method. The phases consist of system planning, system analysis, system design, system implementation and system testing. This website is easily accessible to users using a web browser connected to the Internet network at the address http://lanmas07.masuk.id.